Analisis Pelanggaran HAM di Korea Utara - Tanuwijaya, Patricia; Trianata, Dean; Hasiholan, Yosua (Nusantara: Jurnal Pendidikan, Seni, Sains dan Sosial Humaniora, 2023)
There are many cases of human rights violations that occur in North Korea, such as detention, arrest, and forced labor involving minors, as well as restrictions on freedom of action by the North Korean government. Restrictions on freedom of action by the North Korean government include freedom of speech, freedom to travel abroad, and freedom of access to information. Not only that, the inhumane conditions of detention are also part of the human rights violations committed by the North Korean government. The impact of human rights violations that occur in North Korea has caused many people to experience mental health, such as depression and there are North Koreans who consume illegal drugs such as drugs. With the many cases of human rights violations that have occurred in North Korea, we conducted research with the aim of analyzing the mental health of the North Korean people in conditions where there are many human rights violations, so that this can become a public concern and the problem of human rights violations that occur in North Korea can end soon. In this research, we used a descriptive analytical and normative qualitative method based on a literature study approach. From the results of our research, we found that there are many cases of mental health disorders that occur in North Korean society. Mental health disorders that occurred in North Korean society, such as during the famine that occurred in North Korea in the 1990s. At that time, there was an "Arduous March" which meant doing very hard labor in order to avoid crisis and famine. As a result of this, many North Koreans were traumatized.